ORGANIZATIONAL COMMITMENT AS A MEDIATION FACTOR ON THE RELATIONSHIP BETWEEN TRANSFORMATIONAL LEADERSHIP AND JOB SATISFACTION IN LUXUN ACADEMY OF FINE ART UNDER LIAONING PROVINCE - He, Zhan; Tipanark, Peerapong; Mengman, Pornthep (วารสารวิจัยธรรมศึกษา, 2024)
The objectives of this research were: (1) to propose a model of mediating effects of organizational commitment on the relationship between administrators’ transformational leadership and faculty members’ job satisfaction within Luxun Academy of Fine Art in Liaoning province (2) to evaluate the model fit with the empirical data, and focus to the variables were influenced the job’s satisfaction of faculty members. The total population of this study included 595 faculty members from Luxun Academy of Fine Art. A stratified random sampling method was used to sample, totaling 342 person which calculated from G*Power program. The instrument for collecting data was a questionnaire. Descriptive statistics and inferential statistics were used to perform data analysis by using statistical computer software. Research results revealed that: (1) A mediating effects of organizational commitment relationship between administrator’s transformational leadership and faculty member’s job satisfaction model fit with the empirical data at statistically significant p< 0.01, the value of full model: Chi-square = 61.49, df = 51, p = 0.15, GFI = 0.97, AGFI = 0.96, CFI = 0.99, NFI = 0.98, and SRMR= 0.02. (2) Administrators’ transformational leadership, and faculty members organizational commitment had a directly influence faculty member’s job satisfaction (3) Administrator’s transformational leadership not indirectly influence faculty members job satisfaction through organizational commitment.